Transcription Factors of the Alx Family: Evolutionarily Conserved Regulators of Deuterostome Skeletogenesis - Khor, Jian Ming; Ettensohn, Charles A. (Frontiers in Genetics, 2020)
Members of the alx gene family encode transcription factors that contain a highly conserved Paired-class, DNA-binding homeodomain and a C-terminal OAR/Aristaless domain. Phylogenetic and comparative genomic studies have revealed complex patterns of alx gene duplications during deuterostome evolution. Remarkably, alx genes have been implicated in biomineralization and skeletogenesis in both echinoderms and vertebrates. In this review, we provide an overview of current knowledge concerning alx genes in deuterostomes. We highlight their evolutionarily conserved role in biomineralization and draw parallels and distinctions between the skeletogenic gene regulatory circuitry of diverse groups within the superphylum.